Soil Organic Carbon Stocks Across Different Agroforestry Systems in Coffee-Based Land Use: A Case Study in Malang, Indonesia - Perdana, Andrian; Puspita Sari, Niken; Yuliasmara, Fitria; Erdiansyah, Novie Pranata (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2025)
Agroforestry systems have garnered significant attention for their potential in enhancing soil organic carbon (SOC) stocks, particularly in coffee plantations. The different shading conditions not only diversifies production but also plays a crucial role in soil health and carbon sequestration. The study aimed to investigate the SOC stocks under various coffee-based agroforestry systems. Four different shading conditions have been examined, namely: A (unshaded), B (Leucaena leucocephala shade), C (Pinus sp. shade), and D (complex agroforestry). The results were analyzed descriptively by comparing the influence of varying shading conditions in enhancing SOC stocks. The results indicated that complex agroforestry had the highest SOC (1.33%), followed by L. leucocephala shade (1.20%), unshaded (1.02%), and Pinus sp. shade (0.96%). In the complexagroforestry system, the diversification of plant species increases soil organic matter (SOM) and root biomass, thus improve SOC. Meanwhile, the Pinus sp. shade exhibited the lowest SOC due to the lower quality of its resistant litter. The complex agroforestry also recorded the highest SOC stocks (42.7 t C ha -1), followed by unshaded (39.9 t C ha -1), L. leucocephala shade (38.3 t C ha -1), and Pinus sp. shade (30.5 t C ha-1). The SOC stocks in the unshaded system exceeded those under L. leucocephala shade due to higher bulk density resulting from the absence of complex root systems. Moreover, the complex agroforestry exhibited elevated levels of soil N, P, K, and CEC. These findings implied that complex agroforestry system represents a multifaceted approach to enhance SOC stocks and soil health in coffee plantation.